ANALYSIS OF THE USE OF THE DRAINAGE IMPLANT HEALAFLOW IN SURGERY FOR PRIMARY OPEN-ANGLE GLAUCOMA - Abdurakhimova F.K., (Central Asian Journal of Medicine, 2025)
Primary open-angle glaucoma (POAG) is a progressive optical neuropathy characterized by specific structural changes of the optic disc and visual field defects. Surgical treatment remains the gold standard when conservative therapy is ineffective, but postoperative fibrosis significantly limits the long-term efficacy of filtering surgeries. HealAFlow, an innovative injectable implant based on cross-linked hyaluronic acid, represents a promising solution to this problem. This review analyzes the current clinical data, mechanisms of action, comparative efficacy and safety of HealAFlow in POUG surgery.